Sensitive detection of oxygen using a diffused integrating cavity as a gas absorption cell - Zhou, Xue; Yu, Jia; Wang, Lin; Gao, Qiang; Zhang, Zhiguo (Sensors and Actuators B: Chemical, 2017)
In this study, an oxygen monitoring system was demonstrated for sensitive oxygen detection. The system is based on tunable diode laser absorption spectroscopy (TDLAS) and wavelength modulation spectroscopy (WMS). Stable 2nd-harmonic signals of oxygen were detected by measuring the oxygen P9 absorption line at 764.38. nm. In the detection, a cubic diffuse integrating cavity was employed as a gas absorption cell to increase the optical path length and achieve a higher sensitivity. In addition, to perform automatic gas concentration measurements, a data recording and analyzing program based on the National Instruments LabVIEW software platform was developed. An uncertainty of 0.05% and a detection sensitivity of 350 ppmv were obtained using this system.
Keywords: Absorption spectroscopy; Integrating cavity; Oxygen sensor; Tunable diode laser